Topographical, compositional, and dopant contrast from cleavage surfaces of GaAs-AlxGa1-xAs superlattices - Castell, M; Perovic, D; Howie, A; Ritchie, D; Lavoie, C; Tiedje, T (1995)
We present images of (110) cleavage surfaces of GaAs-AlxGa1-xAs superlattices obtained by scanning force microscopy (SFM) and field-emission scanning electron microscopy. Topographical information is mapped by secondary electrons (SEs) and SFM, compositional differences are imaged through SEs and backscattered electrons (BSEs), and information on dopant type is gained through SEs only. Models are presented explaining the contrast observed in each case.